2004
DOI: 10.1002/pmic.200300653
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of hepatocellular carcinoma cell strains, MHCC97‐H and MHCC97‐L, with different metastasis potentials

Abstract: To better understand the mechanism underlying hepatocellular carcinoma (HCC) metastasis and to search for potential markers for HCC prognosis, differential proteome analysis on two HCC cell strains with high and low metastatic potentials, MHCC97-H and MHCC97-L, was conducted using two-dimensional (2-D) gel electrophoresis followed by matrix-assisted laser desorption/time of flight mass spectrometry and liquid chromatography ion trap mass spectrometry. Image analysis of silver-stained 2-D gels revealed that 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 42 publications
2
94
2
2
Order By: Relevance
“…Finally, calreticulin downregulation has been recently reported to be associated with tumour metastasis (Ding et al 2004). Interestingly, a role for calreticulin has also been demonstrated in regulating p53 function by affecting its rate of degradation and nuclear localization (Mesaeli & Phillipson 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, calreticulin downregulation has been recently reported to be associated with tumour metastasis (Ding et al 2004). Interestingly, a role for calreticulin has also been demonstrated in regulating p53 function by affecting its rate of degradation and nuclear localization (Mesaeli & Phillipson 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased levels of cofilin expression is detected in clinical tumour samples of oral squamous-cell carcinoma 76 , renal cell carcinoma 77 and ovarian cancer 78 using proteomic and cDNA microarray approaches. Expression of the wild-type or the non-phosphorylatable cofilin mutant S3A increases melanoma cell invasion through a reconstituted basement 79 , and in ovarian surface epithelium (OSE) cells derived from women with a family history of ovarian and/or breast cancer and mutations in the BRCA1 tumoursuppressor gene 80 . The regulated overexpression of cofilin inhibits the invasiveness of human lung cancer H1299 cells by disrupting the actin cytoskeleton at the leading edge of the cell 53 .…”
Section: The Cofilin Pathway In Tumour Invasionmentioning
confidence: 99%
“…However, several studies have found that cofilin is downregulated in cancer and that overexpression is antagonistic to invasion. The downregulation of cofilin is observed in MHCC97-H hepatocellular carcinoma (HCC) cells with high meta-static potential 79 , and in ovarian surface epithelium (OSE) cells derived from women with a family history of ovarian and/or breast cancer and mutations in the BRCA1 tumoursuppressor gene 80 . The regulated overexpression of cofilin inhibits the invasiveness of human lung cancer H1299 cells by disrupting the actin cytoskeleton at the leading edge of the cell 53 .…”
Section: The Cofilin Pathway In Tumour Invasionmentioning
confidence: 99%
“…Calumenin transcription was down-regulated in metastatic cells compared to primary tumor cells (43). Calumenin was also down-regulated in hepatocellular carcinoma cells with high metastatic potentials compared to similar cells with low metastatic potentials (44). Mass spectrometry analysis revealed that calumenin could be phosphorylated at Ser-44 and Thr-65 (45,46).…”
Section: +mentioning
confidence: 92%